Socially responsible enterprise marketing management based BSC (the example of enterprises with sales paintwork) - Shegda, M. (Ways to Improve Construction Efficiency, 2015)
The article describes the features of socially - responsible business in today’s market. Reveals the concept and features of modern marketing enterprises. Determined the balanced scorecard of companies that selling paintings materials in the field of social - responsibility. Analyzed the features of introduction of the balanced scorecard for the enterprise of building industry.